Question about Computers & Internet

Open Question

9y-14x=2 then 7x +3y+6x=2y - Computers & Internet

Posted by on

Ad

3 Suggested Answers

6ya6ya
  • 2 Answers

SOURCE: I have freestanding Series 8 dishwasher. Lately during the filling cycle water hammer is occurring. How can this be resolved

Hi,
a 6ya expert can help you resolve that issue over the phone in a minute or two.
Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.
the service is completely free and covers almost anything you can think of.(from cars to computers, handyman, and even drones)
click here to download the app (for users in the US for now) and get all the help you need.
Goodluck!

Posted on Jan 02, 2017

Ad
support146
  • 90 Answers

SOURCE: 6x+5(x+9y)+7y simplify

6x+5(x+9y)+7y
6x+5x+45y+7y <- Distributive property of multiplication
11x+52y < - Simplify

11x+52y - Simplified version
Further learning:
Distributive property of multiplication:
http://www.math.unt.edu/mathlab/emathlab/distributive_property_of_multipl.htm

Posted on Nov 21, 2009

Ad
joeguest2
  • 2080 Answers

SOURCE: what ia the sulution of 3y-6x=-3

To find the solution, first find the value of y for each equation.
Then substitue one equation into the other so that you only the x variable left.
Then just solve for x.
Once you have a value for x, then you can easily solve for y.


So for the first equation:

3y - 6x = -3
3y = 6x - 3

y = 2x - 1


Now for the second equation:

2y + 8x = 10
2y = -8x + 10

y = -4x + 5

Since both equations equal y, they also equal each other, therefore:

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1
6x = 6

x=1

Now substitute x=1 into either original equation:

y = 2x - 1
y = 2 (1) - 1
y = 2 - 1

y = 1


Therefore the solution is x=1 and y=1



Good luck, I hope that helps.


Joe.

Posted on Nov 10, 2011

Add Your Answer

Uploading: 0%

my-video-file.mp4

Complete. Click "Add" to insert your video. Add

×

Loading...
Loading...

Related Questions:

1 Answer

-6x-3y=27


The x intercept is where your line will cross the x axis. Therefore, the value for y at this point is 0. Substitute 0 for y in this equation and solve for x.

6x + 3(0) = 27
x = 27/6
x = 4 1/2

x intercept = (4 1/2, 0)

Follow the same reasoning for the y intercept.

6(0) + 3y = 27
y = 27/3
y = 9

y intercept = (0,9)

Now plot these two points and draw your line through them.

May 18, 2012 | SoftMath Algebrator - Algebra Homework...

1 Answer

What ia the sulution of 3y-6x=-3


To find the solution, first find the value of y for each equation.
Then substitue one equation into the other so that you only the x variable left.
Then just solve for x.
Once you have a value for x, then you can easily solve for y.


So for the first equation:

3y - 6x = -3
3y = 6x - 3

y = 2x - 1


Now for the second equation:

2y + 8x = 10
2y = -8x + 10

y = -4x + 5

Since both equations equal y, they also equal each other, therefore:

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1
6x = 6

x=1

Now substitute x=1 into either original equation:

y = 2x - 1
y = 2 (1) - 1
y = 2 - 1

y = 1


Therefore the solution is x=1 and y=1



Good luck, I hope that helps.


Joe.

Nov 09, 2011 | Texas Instruments TI-84 Plus Silver...

2 Answers

Tom is 5 times as old as todd.In seven years Tom's age will be 6 years more than 3 times as old as Todd. How old is Todd


Todd is 4 years old.

Let Tom's age = X
Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )
X+13 = 3Y + 21
X = 3Y + 8

So if:
X=5Y
and
X=3Y+8

Then:
5Y=3Y+8
2Y=8
Y=4

I hope that helps.

Joe.

Sep 14, 2011 | Office Equipment & Supplies

1 Answer

Michael buys two bags of chips and three boxes of pretzels for 413. He then buys another bag of chips and two boxes of pretzels for 239. Find the cost of each bag of chips and each box of pretzels.


Price of bag of chips s X and price of box of pretzels is Y.
Now you can write following equations:

2X+3Y=413
X+2Y=239

From second equation you know that X is 239-2Y, and you put that in first equation:

2*(239-2Y)+3Y=413

or

-4Y+3Y=413-2*239

Finally we have for Y: Y=65 and X=239-2Y=109.

Aug 13, 2011 | Office Equipment & Supplies

1 Answer

(2x+3y)(3x+2y)


(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y
= 6x^2 + 4xy - 9xy - 6y^2
= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:
2x by 3x = 6x squared
2x by 2y = 4xy
-3y by 3x = -9xy
-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

1 Answer

6x+5(x+9y)+7y simplify


6x+5(x+9y)+7y
6x+5x+45y+7y <- Distributive property of multiplication
11x+52y < - Simplify

11x+52y - Simplified version
Further learning:
Distributive property of multiplication:
http://www.math.unt.edu/mathlab/emathlab/distributive_property_of_multipl.htm

Nov 21, 2009 | Video Game Consoles & Games

2 Answers

3x+8y+ 13z=357.5 16x+9y=326


This is easy. First these brackets ( ) have a three numbers followed by an x y and z, the brackets mean we should multiply the like amounts: but first lets group like amounts by adding them up 3x+16x+6x= 25x then 8y+9y+11y=28y, now z...13z+14z=27z now the otherside of the equation which is always after the equal sign is 326+453=779, so now it is more simplified by combining like amounts:so now we have 25x+28y++27z=779 so now we must balance both sides of thr equation, what we do to the left side of the equal sign, we must also do to the right side of the = sign, so we need to get x by itself, so we minus 25 and are left with just an x, then if we take 25 off of the other side of the = sign, we must take 779-25 so now x is on the left side by itself then the the right side is 754, so now the x is solved X=754, then you do the same for y and z.

Sep 22, 2009 | The Learning Company Achieve! Math &...

2 Answers

X-3y=5 3x-2y=1


2y - x = 3
x = 3y - 5

Add the two equations side by side,

2y - x + x = 3 + 3y - 5

2y = 3y - 2

y = 2

Plug this in the second equation to get x,

x = 3(2) - 5

x = 1

So the solution is x = 1, y = 2

or in ordered pair notation (1, 2)

Jun 29, 2009 | Computers & Internet

5 Answers

Algebra 1


B. 2((2-Y)/3)-Y=3
2(2-Y)-Y=9
4-2Y-Y=9
-3Y=9-4
-3Y=5
-Y=5/3
Y=-1.67

A. 3X+(-1.67)=2
3X-1.67=2
3X=2+1.67
3X=3.67
X=3.67/3
X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

Not finding what you are looking for?
Computers & Internet Logo

Related Topics:

19 people viewed this question

Ask a Question

Usually answered in minutes!

Top Computers & Internet Experts

Doctor PC
Doctor PC

Level 3 Expert

7733 Answers

kakima

Level 3 Expert

102366 Answers

David Payne
David Payne

Level 3 Expert

14161 Answers

Are you a Computer and Internet Expert? Answer questions, earn points and help others

Answer questions

Manuals & User Guides

Loading...